Modeling CAPRI targets 110‐120 by template‐based and free docking using contact potential and combined scoring function. (28th September 2017) - Kundrotas, Petras J.; Anishchenko, Ivan; Badal, Varsha D.; Das, Madhurima; Dauzhenka, Taras; Vakser, Ilya A.
Abstract: The paper presents analysis of our template‐based and free docking predictions in the joint CASP12/CAPRI37 round. A new scoring function for template‐based docking was developed, benchmarked on the Dockground resource, and applied to the targets. The results showed that the function successfully discriminates the incorrect docking predictions. In correctly predicted targets, the scoring function was complemented by other considerations, such as consistency of the oligomeric states among templates, similarity of the biological functions, biological interface relevance, etc. The scoring function still does not distinguish well biological from crystal packing interfaces, and needs further development for the docking of bundles of α‐helices. In the case of the trimeric targets, sequence‐based methods did not find common templates, despite similarity of the structures, suggesting complementary use of structure‐ and sequence‐based alignments in comparative docking. The results showed that if a good docking template is found, an accurate model of the interface can be built even from largely inaccurate models of individual subunits. Free docking however is very sensitive to the quality of the individual models. However, our newly developed contact potential detected approximate locations of the binding sites.